The Influence of Brand Image and Electronic Word of Mouth on Purchase Intention of the Originote Products by Tiktok Users with Brand Trust as a Mediator - Falasifatul Falah; Muzakar Isa (Universitas KH. Abdul Chalim Mojokerto, 2025)
This research explores the effect of brand image and electronic word of mouth (e-WOM) on the purchase intention of Originote products among TikTok users, with brand trust as a mediating factor. Data were collected using an online survey distributed through Google Forms from October 5th, 2024, to December 5th, 2024, yielding 195 valid responses. While the sample size is suitable for a preliminary study, its limitation to respondents from one department and a focus on TikTok users may restrict the generalizability of the findings. Expanding the sample to include participants from diverse backgrounds, platforms, or demographics would provide more representative results. The study found that brand image and e-WOM significantly and positively influence purchase intention, with brand trust mediating this relationship. Future research could explore additional factors such as internship experiences, interpersonal skills, and social support to enhance understanding of the dynamics between brand trust, e-WOM, and purchase intention, contributing to a broader perspective on consumer behavior.